2002
DOI: 10.1063/1.1415448
|View full text |Cite|
|
Sign up to set email alerts
|

On the theory of the strange and unconventional isotopic effects in ozone formation

Abstract: The strange mass-independent isotope effect for the enrichment of ozone and the contrastingly unconventional strong mass-dependent effect of individual reaction rate constants are studied using statistical ͑RRKM͒-based theory with a hindered-rotor transition state. Individual rate constant ratios of recombination reactions and enrichments are calculated. The theory assumes ͑1͒ an ''-effect,'' which can be interpreted as a small deviation from the statistical density of states for symmetric isotopomers, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
186
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(198 citation statements)
references
References 87 publications
8
186
4
Order By: Relevance
“…So that value should be much larger than that if only vibrational energy transfer were considered. If we compare the total internal down-energy transfer ͗⌬E int ↓͘ in Ivanov and Schinke's trajectory work 40 with the values in Gao and Marcus' work [11][12][13] used to fit experimental data, there is only a small difference in ͗⌬E int ↓͘.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So that value should be much larger than that if only vibrational energy transfer were considered. If we compare the total internal down-energy transfer ͗⌬E int ↓͘ in Ivanov and Schinke's trajectory work 40 with the values in Gao and Marcus' work [11][12][13] used to fit experimental data, there is only a small difference in ͗⌬E int ↓͘.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Our interest in the subject was prompted by studies of ozone whose formation and isotopic effects have been of much recent interest. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In general, the formation of a molecule AB is described by A + B AB ‫ء‬ , ͑1͒…”
Section: Introductionmentioning
confidence: 99%
“…An origin of this -effect was discussed elsewhere. 32,33 To calculate rate constant ratios between different reactions, an approximate formalism is given in the present study. The pressure dependence of rate constant ratios and enrichments is also considered.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Rice-RamspergerKassel-Marcus ͑RRKM͒ theory with a master equation approach for the collisional deactivation of the intermediate excited ozone molecules has been applied to study both phenomena. [32][33][34] It was found that the MIF can be explained when an -effect, a non-RRKM effect, [30][31][32][33][34] which reduces dynamically the low-pressure rate constant of the recombination to form symmetric molecules by a factor of compared to that for the asymmetric ones, and a weak collision effect [32][33][34] for the deactivation of excited ozone molecules is also included in the theory. For the unusually large massdependent isotope effect, observed under very special ͑"unscrambled"͒ experimental conditions, the zero-point energy differences in the two dissociation paths of any asymmetric XYZ * isotopomer play the key role, together with the weak collision efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation